Programa educativo Tik Tok en el mejoramiento de la comunicación oral en los estudiantes del tercer grado de secundaria de la Institución Educativa Teniente Manuel Clavero Muga, Punchana 2022 - Reguera Guerra, Nieves Carolina (2024)
The aim of the study was to assess the effect of implementing the educational program TIK TOK on improving oral communication skills among 9th-grade students at Teniente Manuel Clavero Muga Educational Institution. The study employed a quantitative methodology, utilizing a quasi-experimental experimental design with pretest and posttest application. It involved a sample of 70 students, with 35 in the experimental group and 35 in the control group. The study's results indicated that after implementing the educational program, an average of 12.89 ± 1.63 standard deviation was achieved in the experimental group, which was higher than that obtained in the control group. This was statistically validated through the Mann Whitney U test for median differences between the experimental and control groups, yielding a p-value of 0.000. Furthermore, significant differences in clarity, fluency, coherence, persuasion, paraverbals and non-verbal resources were demonstrated in favor of the experimental group.